Analisis Bibliometrik Bidang Kajian Kebugaran Jasmani Pada Skripsi Mahasiswa Program Studi Ilmu Keolahragaan Universitas Negeri Jakarta Tahun 2011-2022 - Wulandari, Nurlaili; Budiningsih , Marlinda; Setiakarnawijaya, Yasep; Kuswahyudi, Kuswahyudi; Amin, Bazuri Fadillah; Oktafiranda, Nadya Dwi (Institut Teknologi Bandung, 2023)
This study aims to map, analyze developments and find future research ideas ideas relatedto physical fitness studies in bachelor of Sports Science program students at StateUniversity of Jakarta. The sampling technique used was a total sample of 513 thesis titlesfor the 2011-2022 publication year, selected from 517 titles obtained from the Jakarta StateUniversity repository page with a data collection period from August to September 2022.Samples were collected using the Comma Separated Value (CSV) format, and the researchwas conducted using the bibliometric analysis method using the VOSviewer application.From 513 titles, 57 keywords were obtained with the criteria of appearing at least 5 timesand producing 8 mapping clusters. The results of the mapping show that physical fitness isa research topic that is often used in thesis research of sports science study programs asindicated by the appearance of 43 times. The results of the analysis recommend ideas forfuture research such as studies on VO2Max, body mass index, nutritional status, andphysical activity or the development of the fields that linked with sports in sports sciencefaculty of State University of Jakarta.